Adverbiers syntaks i ordbøger - Nimb, Sanni (Nordiske Studier i Leksikografi, 2006)
The lexical syntactic properties of Danish adverbs. This paper investigates the individual syntactic properties of Danish adverbs on the basis of recent Scandinavian grammar descriptions as well as extensive corpus investigations. The main goal is to clarify which types of syntactic information to describe in the lexical entries of adverbs, in a computational lexicon as well as in a learners’ dictionary of Danish. On the basis of the investigation, a lexical description model for the word class is proposed and afterwards applied for the description of 217 monosemous adverbs. Five main syntactic groups of Danish adverbs are presented on the basis of the lexicon. But still we find lots of syntactic differences between lemmas belonging to the same group, even between synonymous lemmas which one might expect to have the same syntactic behaviour – this underlines that adverbs have very individual lexical properties.